INFORMATION SYSTEM SALES SHOE STORE IN IVORY - Prasetya, Gandhi Angga; Sukmaaji, Anjik; Subijono, Tony (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
IVORY shop is a shoe store located in Mojokerto. IVORY store outlets have 3 pieces, each of which is located at Jalan Semeru, Mojokerto, Jalan Bhayangkara, Mojokerto, and Jalan Pemuda, Dlanggu, Mojokerto. The shop which was founded in 2009 sells Sneaker type shoes. Control efforts undertaken by management Ivory stores today is to go one by one to three outlets in turn. The supervision by the store management Ivory per day includes: activities of sales per outlet and best-selling products.Based on the above, it is built to store sales information system Ivory. This information system is expected to connect the three outlets Ivory shoe store, so it can assist management in monitoring Ivory store store sales activities in other outlets in realtime.Once completed the system is designed, built, and tested, this information system can display the information activities of sales is going to be able to assist the management in oversee Ivory store sales performance in branches, retail outlets Ivory.Kata Kunci: System Information, Synchronization, Activities Sales, Ivory Store